A decade of insight: bibliometric analysis of gut microbiota’s role in osteoporosis (2014–2024) - Luo, Zhi Qiang; Huang, Ya Jing; Chen, Ze Hua; Lu, Chen Yin; Zhou, Biao; Gong, Xiang Hao; Shen, Zhen; Wang, Tao (Frontiers in Medicine, 2024)
Purpose: Osteoporosis represents a profound challenge to public health, underscoring the critical need to dissect its complex etiology and identify viable targets for intervention. Within this context, the gut microbiota has emerged as a focal point of research due to its profound influence on bone metabolism. Despite this growing interest, the literature has yet to see a bibliometric study addressing the gut microbiota's contribution to both the development and management of osteoporosis. This study aims to fill this gap through an exhaustive bibliometric analysis. Our objective is to uncover current research hotspots, delineate key themes, and identify future research trends. In doing so, we hope to provide direction for future studies and the development of innovative treatment methods.Methods: Relevant publications in this field were retrieved from the Web of Science core collection database (WOSSCC). We used VOSviewer, CiteSpace, an online analysis platform and the R package "Bibliometrix" for bibliometric analysis.: A total of 529 publications (including 351 articles and 178 reviews) from 61 countries, 881 institutions, were included in this study. China leads in publication volume and boast the highest cumulative citation. Shanghai Jiao Tong University and Southern Med Univ are the leading research institutions in this field. Nutrients contributed the largest number of articles, and J Bone Miner Res is the most co-cited journal. Of the 3166 scholars who participated in the study, Ohlsson C had the largest number of articles. Li YJ is the most co-cited author. "probiotics", "Inflammation" are the keywords in the research. Conclusion: This is the first bibliometric analysis of gut microbiota in osteoporosis. we explored current research status in recent years and identified frontiers and hot spots in this research field. we investigate the impact of gut microbiome dysregulation and its associated inflammation on OP progression, a topic that has garnered international research interest in recent years. Additionally, our study delves into the potential of fecal microbiota transplantation or specific dietary interventions as promising avenues for future research, which can provide reference for the researchers who focus on this research filed.